Whey Proteins-Zinc Oxide Bionanocomposite as Antibacterial Films - Paolo Pino; Silvia Ronchetti; Chiara Mollea; Marco Sangermano; Barbara Onida; Francesca Bosco (MDPI AG, 2021)
The use of toxic crosslinking agents and reagents in the fabrication of hydrogels is a frequent issue which is particularly concerning for biomedical or food packaging applications. In this study, novel antibacterial bionanocomposite films were obtained through a simple solvent casting technique without using any crosslinking substance. Films were made from a flexible and transparent whey protein matrix containing zinc oxide nanoparticles synthesised via a wet chemical precipitation route. The physicochemical and functional properties of the ZnO nanoparticles and of the composite films were characterised, and their antibacterial activity was tested against S. epidermidis and E. coli. The synthesised ZnO nanoparticles had an average size of about 30 nm and a specific surface area of 49.5 m2/g. The swelling ratio of the bionanocomposite films increased at basic pH, which is an appealing feature in relation to the absorption of chronic wound exudate. A n-ZnO concentration-dependent antibacterial effect was observed for composite films. In particular, marked antibacterial activity was observed against S. epidermidis. Overall, these findings suggest that this novel material can be a promising and sustainable alternative in the design of advanced solutions for wound dressing or food packaging.